A geometrical approach to spike train noise - Gillespie, James B. (Trinity College (Dublin, Ireland). School of Mathematics, 2012)
Mathematically, spike trains are elusive processes. They encode information, although how this information is contained in a spike train is still not clear. Same-stimulus spike trains display structural similarities, yet noise is also always present, bounding the precision with which a signal can be transmitted. Taking these varied factors into account is difficult, and here a geometrical approach is adopted in developing flexible mathematical descriptions of spike train properties.
Keywords: Mathematics, Ph.D.; Ph.D. Trinity College Dublin.